-(-4m-4)=10+2m

Simple and best practice solution for -(-4m-4)=10+2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-4m-4)=10+2m equation:


Simplifying
-1(-4m + -4) = 10 + 2m

Reorder the terms:
-1(-4 + -4m) = 10 + 2m
(-4 * -1 + -4m * -1) = 10 + 2m
(4 + 4m) = 10 + 2m

Solving
4 + 4m = 10 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
4 + 4m + -2m = 10 + 2m + -2m

Combine like terms: 4m + -2m = 2m
4 + 2m = 10 + 2m + -2m

Combine like terms: 2m + -2m = 0
4 + 2m = 10 + 0
4 + 2m = 10

Add '-4' to each side of the equation.
4 + -4 + 2m = 10 + -4

Combine like terms: 4 + -4 = 0
0 + 2m = 10 + -4
2m = 10 + -4

Combine like terms: 10 + -4 = 6
2m = 6

Divide each side by '2'.
m = 3

Simplifying
m = 3

See similar equations:

| 4/10x=2/(3x-14) | | -4x-x=25 | | 10+y-5y=0 | | 2x=7x-72 | | 3-6=15x+18 | | 3x^2+3Y^2-108=0 | | 8x-9xy= | | 3x^2+3Y^2-108=8 | | 3-6=15x+188 | | -5-3p=-5-6(p-1) | | 11/x=4-1/x | | Log(6)(3x)+Log(6)(x-1)=3 | | f(x)=-2x^2+5x+7 | | 5(2x-1)=7x+16 | | 6Log(3x)+6Log(x-1)=3 | | 5X+7=3X+43 | | 25m^2-36n^2=0 | | 2+8(1-9n)=-34 | | 8(6v-5)=v+7 | | x+(2.9)=9.1 | | 8(m-3)=4(4-1) | | x^2+x^3-150=0 | | f(x)=2x^2+5x+7 | | x+(7)=1 | | x/2-6=x/5 | | y=5x^2/3x-2 | | x-(6.1)=3.1 | | 5v-2v=12 | | x+(4.1)=1.9 | | 6(1+8y)=18 | | x+(7.9)=4.1 | | x-(3.1)=4.1 |

Equations solver categories